2020
DOI: 10.1080/21501203.2020.1823509
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus niger LBM 134 isolated from rotten wood and its potential cellulolytic ability

Abstract: Aspergillus: is a genus of filamentous and cosmopolitan fungi that includes important species for medical mycology, food, basic research and agro-industry areas. Aspergillus section Nigri are efficient producers of hydrolytic enzymes such as cellulases that are employed in the cellulose conversion. Hence, the search of new cellulolytic isolates and their correct identification is important for carrying out safe biotechnological processes. This study aimed to characterise the cellulolytic potential of Aspergill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…There were previous studies on the enzymatic hydrolytic ability of Aspergillus fungi that were isolated from the Paranaense rainforest (Argentina), and the ability of these fungi to undergo cell degradation was evaluated using Congo staining and uorescence panel tests for carboxymethylcellulase, betaglucosidase, and cellobiohydrolase; all the results were positive. This study demonstrated the ability of Aspergillus fungi to process cellulosic biomass (Díaz et al 2021).…”
Section: Figure (7)mentioning
confidence: 70%
“…There were previous studies on the enzymatic hydrolytic ability of Aspergillus fungi that were isolated from the Paranaense rainforest (Argentina), and the ability of these fungi to undergo cell degradation was evaluated using Congo staining and uorescence panel tests for carboxymethylcellulase, betaglucosidase, and cellobiohydrolase; all the results were positive. This study demonstrated the ability of Aspergillus fungi to process cellulosic biomass (Díaz et al 2021).…”
Section: Figure (7)mentioning
confidence: 70%
“…Also, some Aspergillus sp. reported to have the potential cellulolytic ability are Aspergillus niger [12] , A. fumigatus [13] , A. aculeatus [14] . Hypothetically, the addition of a cellulolytic Aspergillus sp.…”
Section: Introductionmentioning
confidence: 99%
“…The degradation and utilization of cellulose by fungi not only plays a positive role in the carbon cycle, but also brings great commercial value in industrial production [ 1 3 ]. At present, many scholars have explored filamentous fungi, such as Trichoderma reesei, Penicillium oxalicum , and Aspergillus niger in enzyme production [ 4 6 ]. By using cellulose as raw materials to efficiently produce cellulase, it was found that the mycelial growth in the process of decomposing cellulose was promoted [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…At present, many scholars have explored filamentous fungi, such as Trichoderma reesei, Penicillium oxalicum , and Aspergillus niger in enzyme production [ 4 6 ]. By using cellulose as raw materials to efficiently produce cellulase, it was found that the mycelial growth in the process of decomposing cellulose was promoted [ 4 6 ]. As macro-fungi, mushrooms are also an important agent of degradation of cellulose [ 7 ].…”
Section: Introductionmentioning
confidence: 99%